Managing Emerging (Mis)Alignments in Data-Driven Servitization. Issue 4 (4th July 2019) - Altmann, Peter; Linder, Marcus
Overview: Manufacturers moving to service-based business models are generally advised to provide total-care solutions to their customers in order to boost profits and strengthen customer relationships. To reduce the risks associated with such services, service providers often rely on remote monitoring technologies to access data on their products' health and usage. Our study reveals a tension between the technical development of complex products capable of remote monitoring and the business logic required to commercialize this potential. Specifically, we show that the collaborative value co-creation context within which these products are typically developed requires managers to seek alignment in technical specifications and value co-creation logics simultaneously. However, technical alignment is contingent on factors that can lead to business logic misalignments.